Recent developments in nucleic acid-based therapies for Parkinson’s disease: Current status, clinical potential, and future strategies - Pandey, Shivam Kumar; Singh, Rakesh Kumar (Frontiers in Pharmacology, 2022)
Parkinson’s disease is the second most common progressive neurodegenerative disease diagnosed mainly based on clinical symptoms caused by loss of nigrostriatal dopaminergic neurons. Although currently available pharmacological therapies provide symptomatic relief, however, the disease continues to progress eventually leading to severe motor and cognitive decline and reduced quality of life. The hallmark pathology of Parkinson’s disease includes intraneuronal inclusions known as Lewy bodies and Lewy neurites, including fibrillar α-synuclein aggregates. These aggregates can progressively spread across synaptically connected brain regions leading to emergence of disease symptoms with time. The α-synuclein level is considered important in its fibrillization and aggregation. Nucleic acid therapeutics have recently been shown to be effective in treating various neurological diseases, raising the possibility of developing innovative molecular therapies for Parkinson’s disease. In this review, we have described the advancements in genetic dysregulations in Parkinson’s disease along with the disease-modifying strategies involved in genetic regulation with particular focus on downregulation of α-synuclein gene using various novel technologies, notably antisense oligonucleotides, microRNA, short interfering RNA, short hairpin RNAs, DNA aptamers, and gene therapy of vector-assisted delivery system-based therapeutics. In addition, the current status of preclinical and clinical development for nucleic acid-based therapies for Parkinson’s disease have also been discussed along with their limitations and opportunities.